To be lonely and to be alone: a liberating change of attitude - Vicheva, Violeta (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
This paper deals with the literary representation of loneliness in the novel “Traurige Freiheit” by Friederike Gössweiner. The analysis is carried out in contrast to the illness and crisis discourse in which loneliness and being alone are repeatedly embedded today. The interpretation of the novel offered opens up a new perspective on the topic, which the critical reception of the work has so far left unreflected and which aims at destigmatizing being alone through the social transformation potential of literature.